Von der Freiheit, Schmerz zu spüren - Bromm, Burkhart; Wolf, Jörn Henning; der Wissenschaften, Akademie (Abhandlungen der Akademie der Wissenschaften in Hamburg, 2017)
We can make our pain more bearable through our will. But how and where does my self (my mind) affect my body? In this books, medical doctors, neurophysiologists, physicists, and psychologists show that the dualism of body and mind we all experience does not really exist. Body and mind are an indivisible unit, shaped over millions of years by the adaptive self-organization of the brain`s neuronal networks.